Evolution of Freight Villages and Dry Ports from the Macro Logistics Perspective Based on European Benchmarking 2020 - Oláh, Judit; Nestler, Steffen; Nobel, Thomas; Popp, József (Periodica Polytechnica Transportation Engineering, 2021)
Being the initiator of the German and European Freight Village ranking, Deutsche GVZ-Gesellschaft (DGG) has the methodical know how to create the benchmarking studies. In this ranking approximately 100 Freight Village locations were analysed and evaluated. The research was based on the generation of an uniform understanding, which was focused on intermodality and the significant distinctive management structures. This data led to a qualitative and detailed overview. Because of the positive response, we were motivated to start the second ranking in 2015, as well as the update in 2019/2020. The results of the ranking show important basics and facts, which demonstrate the importance of the Freight Villages and strengthened their role as central, intermodal logistics nodes. Moreover, the responsible decision makers in the Freight Villages benefit from the results of the benchmarking. Many management companies use their placement in the ranking for public relations activities. Good placements or improvements are important instruments in marketing strategies.